Opioid Prescribing Practices of Orthopaedic Surgeons: Results of a National Survey. Issue 4 (15th February 2019) - Raneses, Eli; Secrist, Eric S.; Freedman, Kevin B.; Sohn, David H.; Fleeter, Thomas B.; Aland, Christopher M.
Abstract : Introduction: Opioids are widely used after orthopaedic procedures. Nonmedical opioid use is a growing public health issue. Methods: An anonymous online survey was distributed by e-mail to the orthopaedic societies of all 50 states and several large private practices to assess practicing orthopaedic surgeons' opioid prescribing practices. Results: A total of 555 orthopaedic surgeons practicing in 37 states responded. The most commonly prescribed opioid for both teenagers and adults was hydrocodone/acetaminophen. Of note, 42.3% reported that a patient they have prescribed opioids for developed an opioid dependency, whereas 35.3% do not believe that opioid use is a problem in their practice. Of note, 30.3% reported prescribing refills, and factors significantly associated with increased prescribing of refills included a greater number of years in practice ( P < 0.001) and practicing in a suburban rather than an urban or rural environment ( P = 0.03). Conclusion: Orthopaedic surgeons rarely prescribe any refills, tend to prescribe less opioids to teenagers than adults, and prescribe fairly uniformly for patients who are treated nonsurgically or undergo minor or arthroscopic surgery. They exhibit considerable variation in prescribing for fractures and major procedures.